Slower Snowmelt in Spring Along With Climate Warming Across the Northern Hemisphere. Issue 22 (20th November 2018) - Wu, Xuejiao; Che, Tao; Li, Xin; Wang, Ninglian; Yang, Xiaofan
Abstract: Climate warming is altering historical patterns of snow accumulation and ablation, hence threatening natural water resources. We evaluated the impact of climate warming on snowmelt rates using the GlobSnow v2.0 and the second Modern‐Era Retrospective analysis for Research and Applications data sets over the Northern Hemisphere (NH) during the past 38 years (1980–2017). Higher ablation rates were found in the locations with deeper snow water equivalent (SWE) because high snow melt rates occurred in late spring and early summer in deep snowpack regions. In addition, due to the reduction of SWE in deep snowpack regions, moderate and high snow ablation rates showed a decreasing trend. Therefore, slower snowmelt rates were found over the entire NH in a warmer climate in general. Based on projections of SWE in Representative Concentration Pathways 2.6, 4.5, and 8.5 climate scenarios, slower snowmelt rates in the NH may continue to happen in the future. Plain Language Summary: Snowmelt is a major fresh water resource that supplies human lives and ecosystems in the Northern Hemisphere (NH). Recent climate warming has altered the patterns of snow distribution and snowmelt processes. However, such processes are poorly understood. In the current research, we investigated the snowmelt rates over the NH between 1980 and 2017 using the GlobSnow v2.0 and the second Modern‐Era Retrospective analysis for Research and Applications data sets. In contrast to previous hypotheses, we found that slower snowmelt rate has occurred with climate warming, which can be explained by the decrease of snow water equivalent in deep snowpack regions. Based on the projected snow water equivalent data sets in this century, we also predicted that slower snowmelt rates in the NH may continue to happen in the future. Our analyses also indicated that slower snowmelt would decrease spring runoff and influence vegetation phenology and ecological processes. Key Points: Slower snowmelt rates were found over the North Hemisphere (NH) in the past 38 years with climate warming Based on the projection of snow water equivalent (SWE), slower snowmelt rates may continue to happen in the future Slower snowmelt will impact spring streamflow, vegetation phenology, and ecological processes